Modified fibrous silica for enhanced carbon dioxide adsorption: Role of metal oxides on physicochemical properties and adsorption performance - S. M., Yusof; R., Othaman; Setiabudi, H. D.; L. P., Teh (Elsevier Ltd, 2021)
This work investigates the effectiveness of FS loaded with CaO, MgO, and CeO2 for CO2 adsorption. Different techniques such as XRD, ATR–FTIR, Raman, CO2–TPD, in situ FTIR, FESEM, and TEM were employed. Upon the metal oxides loading, the alteration of textural properties, increases in the weak and moderate basic strength and quantity of basic active sites as well as disappearance of the dendritic structures in CaO/FS were observed. The in situ FTIR studies confirmed the formation of different carbonates species upon the interaction with CO2. The greatest CO2 physisorption capacity was demonstrated by CaO-FS (0.76 ​mmol/g), while the highest CO2 chemisorption uptake was shown by MgO-FS (9.77 ​mmol/g). The CO2 physisorption activity depends mainly on the porosity and basic strength of the adsorbents. On the contrary, the CO2 chemisorption performance is determined by the basic strength and basic sites as well as CO2 affinity of the adsorbents.